2023
DOI: 10.1021/jacs.3c06396
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Solvent Exchange Kinetics in a MOF with Coordinatively Unsaturated Sites

Hochul Woo,
Angela M. Devlin,
Adam J. Matzger

Abstract: Solvent exchange of synthesis solvent within metal− organic frameworks (MOFs) is an essential process for the activation of coordinatively unsaturated sites (CUS) to achieve an optimal surface area; activation of the CUS is required to exploit the versatile applications of MOFs. However, it is challenging to replace CUS-bound synthesis solvent prior to MOF activation, which can lead to a structural collapse and reduced surface area post-evacuation. Herein, we quantify the exchange behavior of a copper paddlewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…When the coordinated ligand in an octahedral complex is replaced, a dissociative mechanism is generally operative; , this mechanism involves a reduced coordination number of the intermediate during the ligand replacement, making the exchange rate independent of the nature of the entering ligand. In such cases, the substitution of CUS-bound solvents proceeds at similar rates regardless of the exchange solvent, as observed in the case of copper paddlewheel MOFs . However, if the solvent exchange follows an associative mechanism, then, the solvent exchange rate is sensitive to the nature of the entering ligand.…”
Section: Results and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…When the coordinated ligand in an octahedral complex is replaced, a dissociative mechanism is generally operative; , this mechanism involves a reduced coordination number of the intermediate during the ligand replacement, making the exchange rate independent of the nature of the entering ligand. In such cases, the substitution of CUS-bound solvents proceeds at similar rates regardless of the exchange solvent, as observed in the case of copper paddlewheel MOFs . However, if the solvent exchange follows an associative mechanism, then, the solvent exchange rate is sensitive to the nature of the entering ligand.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Unlike the copper paddlewheel MOFs , that exhibit metal–metal stretching frequencies, M 2 (dobdc) does not display such vibrations. Instead, the stretching frequency of phenolate CO, which coordinates directly to the metal, is measured to indirectly monitor the change in the metal–solvent interaction.…”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Practically, MOFs are reported to release metal ions and ligands in water media, concurrently experiencing structural reconstruction stimulated by electrochemical environment. Furthermore, it has been observed that MOFs undergo surface reconstruction to generate oxyhydroxides during glucose electrocatalytic oxidation. These phenomena raise two critical inquiries: first, the veritable source of catalytic activity governing glucose oxidation and, second, the extent to which this reconstruction transpires, whether it remains confined to the surface of MOFs or penetrates deeper as the reaction proceeds. Nevertheless, these aspects have not been explored in depth within the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of the PSE process are complex and not fully understood, though recent research has begun to elucidate some aspects. Factors influencing PSE include a choice of solvent, reaction time, , temperature, ,,, and the functional groups ,, on the linker. The particle size of the original MOF used in the PSE process is also crucial and typically remains unchanged after PSE. ,,,, Nair and co-workers demonstrated that, under identical reaction conditions, the incorporation rate for nanoparticles significantly increases compared to the micrometer-sized crystals .…”
Section: Introductionmentioning
confidence: 99%